Malka sheharzdad - Iqbal kardad (Ferozsons (Pvt) Limited ; PAKISTAN, 1998)
"Malka Sheharzad" is a captivating tale of wisdom, courage, and storytelling, centered on the legendary queen whose narratives transform lives and reveal the power of intellect and compassion in overcoming adversity.